The Modern Concept of the State and the Transformation of the Greek Polis into a State (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
This contribution suggests a proper definition of the state. It refuses the limitation of the term to modern states only and sees the state as a concept for all historical epochs. The definition takes up the doctrine of the three elements constituting the state: territory, people and power (Georg Jellinek), but adds necessary specifications and amendments. The article discusses further the position of Max Weber and criticizes recent publications of ancient historians.
Keywords: State; statehood; institutions; legitimacy; sovereignty